Ultra-low-power super class-AB adaptive biasing operational transconductance amplifier with enhanced gain for biomedical applications - Pandey, Rakesh Kumar; Bhadauria, Vijaya; Singh, Vinod Kumar (Bulletin of Electrical Engineering and Informatics, 2024)
The operational transconductance amplifier (OTA) proposed in this article is a bulk-driven (BD), single-stage, super-class-AB, adaptive biasing, functioning in the subthreshold region (ST) with an enormously low power supply of ± 0.25 V, providing high-gain. The input core of the OTA circuit is composed of adaptively biased BD differential input pairs based on flipped voltage follower (FVF), which drive in class-AB mode with a partial positive feedback (PPF) approach. The circuit additionally employs FVF and self-cascode (SC)-based low-power current mirror loads at its output to obtain significantly high gain and unity gain frequency. In addition, using adaptive loads based on source-degenerated metal oxide semiconductor (MOS) resistors raises dynamic current more efficiently, consequently improving the slew rate and unity gain frequency (UGF) without drawing additional power. Employing the cadence spectre tool and the UMC 0.18 μm complementary metal oxide semiconductor (CMOS) process technology, the designed OTA has been simulated. The simulation outcomes substantiate that the amplifier provides high open loop DC gain of 75 dB, 18.75 kHz UGF with a phase margin of 63.93º, and input-referred noise (IRN) of 0.734 µV/Hz0.5 at 1 kHz frequency. The proposed OTA consumes just 60.15 nW of power. The performance results confirmed that the proposed OTA circuit is appropriate in biomedical applications.